Upaya Meningkatkan Hasil Belajar Perkalian Bilangan Bulat dengan Menggunakan Media Gambar Siswa Kelas II UPTD SD N 01 Suayan Kecamatan Akabiluru Tahun Pelajaran 2022/ 2023 - Erninda Erninda (Departement of Mathematics Education, 2023)
This research is motivated by the importance of learning mathematics in elementary schools which functions to help students to calculate what is needed in life in society by using mathematics, discovering and using analytical abilities and imagination. However, students were not optimal in multiplication so that it became a problem in learning Mathematics in class II UPTD SD Negeri 01 Suayan, Akabiluru District. This study aims to determine the increase in learning outcomes to calculate the multiplication of integers using media images in class II UPTD SD Negeri 01 Suayan, Fifty City District. The implementation of this research used classroom action research which was carried out in collaboration between class II teachers as researchers and other class teachers as observers in the research. This research was conducted in two research cycles with the planning, action, observation, and reflection stages. Learning to count multiplication utilizes image media as a learning medium. Subject taking as many as 21 students, which are then divided into several small groups. The results of this study indicate that (1) Learning to use media images can improve students' skills in calculating multiplication and increase student activity in learning with the percentage of calculating multiplication before carrying out actions of 48.41% and Cycle I of 66.67% and Cycle II of 83.33%. (2) learning by utilizing media images can increase student activity in learning. (3) Learning can improve the ability and creativity of teachers in learning. (4) Errors made by students in calculating multiplication can be overcome by using media images. From the results of the research, it is suggested to educational institutions to use pictures as learning media for calculating multiplication.